1997
DOI: 10.1038/385165a0
|View full text |Cite
|
Sign up to set email alerts
|

Role of melanocortinergic neurons in feeding and the agouti obesity syndrome

Abstract: Dominant alleles at the agouti locus (A) cause an obesity syndrome in the mouse, as a consequence of ectopic expression of the agouti peptide. This peptide, normally only found in the skin, is a high-affinity antagonist of the melanocyte-stimulating hormone receptor (MC1-R), thus explaining the inhibitory effect of agouti on eumelanin pigment synthesis. The agouti peptide is also an antagonist of the hypothalamic melanocortin-4 receptor (MC4-R). To test the hypothesis that agouti causes obesity by antagonism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

44
1,242
11
20

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 1,766 publications
(1,317 citation statements)
references
References 25 publications
44
1,242
11
20
Order By: Relevance
“…More recently, the application of pharmacological studies and molecular biology techniques has identified α-MSH as an important hypothalamic satiety signal [11,28]. The MC3R is expressed in both central and peripheral tissues and although the physiological role for this MCR has not yet been identified, it is the MCR with the greatest affinity for γ-MSH and it appears to mediate some aspects of the central control of blood pressure [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the application of pharmacological studies and molecular biology techniques has identified α-MSH as an important hypothalamic satiety signal [11,28]. The MC3R is expressed in both central and peripheral tissues and although the physiological role for this MCR has not yet been identified, it is the MCR with the greatest affinity for γ-MSH and it appears to mediate some aspects of the central control of blood pressure [32].…”
Section: Introductionmentioning
confidence: 99%
“…The MC4R is expressed in virtually all brain regions and the distribution of this MCR in the CNS is both different and wider than that of the MC3R. Furthermore, the MC4R has been implicated in feeding behaviors and weight homeostasis [9,11,43]. Targeted deletion of the MC5R gene has implicated that this MCR subtype is involved in the coordination of exocrine gland function [6].…”
Section: Introductionmentioning
confidence: 99%
“…The brain MC system comprises of (a) proopiomelanocortin (POMC) neurons in the arcuate nucleus (ARC) and nucleus of the solitary tract [9,17]; (b) agouti-related protein (AGRP) neurons in the ARC [4,20] and (c) melanocortin 3 and 4 receptors (MCRs), which are widely distributed throughout the brain [16,36,39]. Stimulation of the MC system by intracerebroventricular (icv) infusion of a-melanocyte-stimulating hormone (a-MSH) or its analogs results in hypophagia [13,46]. a-MSH infusion raises metabolic rate, increases sympathetic nerve traffic to brown adipose tissue and stimulates lipolysis in ob/ob mice and wildtype rats [15,23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a-MSH treatment influences HPA axis activity by increasing adrenocorticotropin (ACTH) and corticosterone release in rats [10,48]. These effects can be antagonized by treatment with the competitive MC antagonist SHU9119 [1,13,41]. Furthermore, the inverse agonist AGRP (83-132) increases food intake, decreases oxygen consumption and reduces capacity of brown adipose tissue to expend energy [19,32,43].…”
Section: Introductionmentioning
confidence: 99%
“…Leptin also inhibits the orexigenic neurons expressing neuropeptide Y (NPY) and AGRP. 2,4,5 The importance of MC4R in the etiology of obesity was first demonstrated through the inactivation of this receptor in mice. Mice lacking the receptor develop a maturity-onset obesity syndrome associated with hyperphagia, hyperinsulinemia and hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%